I Interactive Contextual-Based Physics E-Module on Temperature and Heat Material to Enhance Middle School Students' Understanding - Azhari, Gloria; Aminoto, Tugiyo; Aj, Suharli (KUANTUM: Jurnal Pembelajaran dan Sains Fisika, 2025)
This research aims to develop contextual-based interactive physics e-modules on temperature and heat materials for junior high school students. Learning media that is still dominated by conventional teaching materials makes it difficult for students to understand concepts concretely and less motivated to learn independently as a solution to increase student learning motivation. Therefore, the development of digital-based learning media is expected to be an effective solution to improve student motivation and quality of understanding. The research uses the Research and Development (R&D) method with a 4D (Define, Design, Develop, Disseminate) model. The subjects of the study were 39 grade VIII students of SMP Negeri 44 Tanjung Jabung Barat. Data collection techniques are carried out through student needs questionnaires and interviews with science teachers, as well as instrument validation by material experts and media experts. Data analysis used quantitative descriptive techniques. The results of the study show that the majority of students use interactive digital learning media to improve their understanding. The development of e-modules is equipped with texts, images, learning videos, practice questions. This study recommends the use of contextual-based interactive e-modules as an innovative learning media solution to support the understanding and learning motivation of physics students in junior high school. This study recommends the use of contextual-based interactive physics e-modules as innovative learning media that can support the teaching and learning process and empower students to learn independently and meaningfully.